2017
DOI: 10.3991/ijim.v11i2.6555
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Virtual Reality in Improving Communication Skills in Children with Autism

Abstract: Abstract-Individuals in the Autism Spectrum often encounter situations where they have to respond to questions and situations that they do not know how to respond to, such as, questions asked by strangers including ones related to daily-life activities. A variety of research has been done to improve social and communication impairments in children with autism using technology. Immersive virtual reality is a relatively recent technology with a potential to bring an effective solution and used as a therapeutic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Due to the 360-degree virtual environment, a participant would have to turn his/her head up to 60 degrees left or right to see all avatars in the scene. Vizard is also used in [44,58] to create virtual reality scenes.…”
Section: Virtual Reality Systems/devicesmentioning
confidence: 99%
“…Due to the 360-degree virtual environment, a participant would have to turn his/her head up to 60 degrees left or right to see all avatars in the scene. Vizard is also used in [44,58] to create virtual reality scenes.…”
Section: Virtual Reality Systems/devicesmentioning
confidence: 99%
“…Eleven studies proposed one task, three studies proposed two tasks, three studies proposed three tasks, one study proposed four tasks, and one study proposed seven tasks. Overall, the proposed tasks can be categorized as follows: matching games whose aim is to correctly associate items [ 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]; daily routine games whose aim is to exercise in tasks such as activities of daily living, shopping, greeting, drawing, evacuating by fire, signs recognizing, eye gazing [ 23 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]; collaborative games whose aim is to cooperate to complete some tasks [ 15 , 16 ]; mathematical games whose aim is to correctly perform arithmetical operations [ 48 ]; labyrinth games whose aim is to correctly reach the end of the path [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, used stimuli include pictures, words, numbers, and avatars. Among studies involving one task, one study used a matching game with geometric pictures stimuli [ 34 ]; one study used a mathematical game with numerical stimuli [ 48 ]; one study used a daily routine game with avatar stimuli [ 42 ]; two studies used a matching game with picture stimuli [ 35 , 36 ]; four studies used a daily routine game with picture stimuli [ 43 , 44 , 46 , 47 ]; one study used a daily routine game with picture and word stimuli [ 45 ]; one study used a labyrinth game with picture stimuli [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that verbal communication is an important factor for acceptability by users . VR is being studied as a method for improving communication skills and stimulus response in certain settings …”
Section: Development Processmentioning
confidence: 99%